Comment on "Modeling for predicting survival fraction of cells after ultra-high dose rate irradiation" - Liew, Hans; Mairani, Andrea (Physics in medicine and biology, 2024)
We comment on the recently published study "Modeling for predicting survival fraction of cells after ultra-high dose rate irradiation" by Shiraishi et al. While the general approach of the study may be appropriate, we wish to comment on its limitations and point out issues concerning their choice of the benchmarking and fitting data. The approach by the authors could become viable in an extended form once more comprehensive data is available.